How innovations catalyse the circular economy: building a map of circular economy innovation types from a multiple-case study - Engez, Anil (Edward Elgar Publishing, 2021)
Technology and business developers are increasingly focusing on innovation development that can improve resource efficiency, which can enable them to pursue competitive advantage through environmental sustainability. The circular economy (CE) needs extensive and diverse innovation that promotes material circulation and waste reduction based on reduce-reuse-recycle principles. Therefore, this chapter aims to uncover several types of CE innovations, the sustainability issues they target, and the pursued benefits. It employs an explorative multiple-case analysis strategy and maps 27 innovative CE offerings by various companies. The study develops a detailed categorization of the following main CE innovation types: novel recycled materials (product innovations), sustainable production processes (process innovations), services for lengthening product lifecycles (service innovations), and business models for reusing and sharing products (business model innovations). Such categorization can guide managers in (re-)designing value propositions and business models in line with sustainable development goals.